2018
DOI: 10.1016/j.psychres.2018.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Recent suicide attempts and serum lipid profile in subjects with mental disorders: A cross-sectional study

Abstract: Background: Subjects with mental disorders have a higher risk of suicide behaviors than the general population. So, to date, researchers have investigated some biomarkers possibly related to suicidality. Despite many studies have reported a possible relationship between low lipid serum levels and suicide attempt, conflicting results have emerged. Aim We investigated whether serum total cholesterol, LDL cholesterol and triglycerides are associated with recent suicide attempts in subjects with different mental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
(68 reference statements)
0
27
0
Order By: Relevance
“…While these findings make a strong case for an association between low total cholesterol level and suicidal behavior, other studies have reported no association between serum cholesterol and suicide [3741], or association in the opposite direction [20, 42]. The first possible explanation for these inconsistent results may be due to different time frames for suicide among different studies.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…While these findings make a strong case for an association between low total cholesterol level and suicidal behavior, other studies have reported no association between serum cholesterol and suicide [3741], or association in the opposite direction [20, 42]. The first possible explanation for these inconsistent results may be due to different time frames for suicide among different studies.…”
Section: Discussionmentioning
confidence: 81%
“…Second, different definitions for suicide have been used in previous studies, including suicidal thoughts or ideation, plans, and death [20, 37, 42]. Third, in our current study we focused only on major depressive disorder, excluding those bipolar disorder [39], general population [20, 42] and other mental disorders [37, 38, 41], which are different from the previous studies. Fourth, other associated factors with suicide attempts were not included in most of previous studies, while our current study included several new clinical and psychological factors.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the present study showed that serum UA levels significantly decreased in only MDD patients with suicide risk, and not in those without suicide risk. More recent evidence indicates that UA levels have a strong negative association with the severity of depressive symptoms [44,50], while depression severity is one of most important risk factors for suicide [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies fail to identify any correlation between serum lipids level and depression (Deisenhammer et al, 2004; Tanskanen et al, 2000; McCallum et al, 1994). Other studies did not find any association between suicidality and lipid profile in major depressive disorder (Bartoli et al, 2017a; Capuzzi et al, 2018). Other reports suggest that depression is associated with higher serum cholesterol level (Moreira et al, 2017; Nakao & Yano, 2004; Ledochowski et al, 2003).…”
Section: Introductionmentioning
confidence: 83%